MENUMBUHKAN KECINTAAN TERHADAP AL-QUR’AN MELALAUI LOMBA HAFALAN DAN QIRA’AT DI DUSUN KRANDEGAN - Bariroh, Nur A’imatul; Majidun, Ahmad; Azizah, Laili Dina; Rohmat, Ali (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
This community service activity at TPQ Al-Amin, Krandegan Hamlet, was conducted in response to the decline in students' motivation to study the Al-Qur'an following the hiatus of religious extracurricular activities. The program aims to rekindle students' love for the Al-Qur'an through positive competition stimuli, specifically short surah memorization and qira'at (recitation) contests. The method employed is a participatory-collaborative approach involving local teachers (ustadz) as primary mentors, while the service team served as technical facilitators. The stages included preparation, intensive coaching, the competition, and evaluation. The novelty of this program lies in the integration of Islamic singing methods (nasyid) as a motivational instrument to reduce anxiety and enhance the students' mental readiness during the coaching phase. Results indicated a significant increase in learning enthusiasm; students became more active in independent muroja'ah (repetition), with an average increase of 2-3 new surahs per student. The synergy between the service team and local teachers successfully reactivated the religious ecosystem at TPQ Al-Amin independently and sustainably.